THE IMPACT OF ARTIFICIAL INTELLIGENCE ON PERSONALIZED LEARNING IN ENGLISH LANGUAGE EDUCATION (International Congress on Economics, Management and Business Studies, 2026)
The integration of Artificial Intelligence (AI) into education has transformed teaching and learning processes worldwide. In English Language Education, AI technologies have introduced innovative approaches to personalized learning by adapting educational content, providing immediate feedback, and supporting individual learning needs. This article explores the impact of AI on personalized learning in English language teaching, highlighting its benefits, challenges, and future prospects. The study argues that AI-powered tools enhance language acquisition, increase learner autonomy, and improve educational outcomes through data-driven instruction and adaptive learning environments.
Keywords: Artificial Intelligence, Personalized Learning, English Language Education, Adaptive Learning, Educational Technology, Language Acquisition. Introduction